2019
DOI: 10.1111/ppa.12997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Lasiodiplodia theobromae from different hosts in northeastern Brazil and Mexico

Abstract: Lasiodiplodia theobromae is one of the most frequent fungal pathogens associated with dieback, gummosis, leaf spot, stem‐end rot and fruit rot symptoms in cashew, mango, papaya and grapevine. In this study, the variation in the genetic diversity of 117 L. theobromae isolates from northeastern Brazil (n = 100) and Mexico (n = 17), which were collected from these four crops, was analysed using microsatellite markers. The results revealed low genetic diversity among L. theobromae populations and the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Among the geographic populations of D. bulgarica, UR had the highest gene and genotypic diversity as well as genotype richness, suggesting that this population may have been the initial founding population and served as a source for subsequent Linde, 2002;Milgroom, 1996). Therefore, high genotypic diversity in populations of supposedly asexual fungi has been considered as an indirect evidence for occurrence of recombination during parasexual or cryptic sexual cycles (Baskarathevan et al, 2012;Bihon et al, 2012aBihon et al, , 2012bRêgo et al, 2019). The high levels of genotypic diversity and richness observed in the present study as well as the low levels of CF, absence of widely distributed dominant genotype, and presence of reticulations in Neighbor-Net could suggest that D. bulgarica populations have not been under strict asexual reproduction and genetic recombination has occurred in the life cycle of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the geographic populations of D. bulgarica, UR had the highest gene and genotypic diversity as well as genotype richness, suggesting that this population may have been the initial founding population and served as a source for subsequent Linde, 2002;Milgroom, 1996). Therefore, high genotypic diversity in populations of supposedly asexual fungi has been considered as an indirect evidence for occurrence of recombination during parasexual or cryptic sexual cycles (Baskarathevan et al, 2012;Bihon et al, 2012aBihon et al, , 2012bRêgo et al, 2019). The high levels of genotypic diversity and richness observed in the present study as well as the low levels of CF, absence of widely distributed dominant genotype, and presence of reticulations in Neighbor-Net could suggest that D. bulgarica populations have not been under strict asexual reproduction and genetic recombination has occurred in the life cycle of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic diversity in a number of Botryosphaeriaceae species belonging to Botryosphaeria , Diplodia , Lasiodiplodia , and Neofusicoccum have been evaluated using various molecular markers such as amplified fragment length polymorphism (AFLP; Al‐Sadi et al, 2013), inter‐simple sequence repeat (ISSR; Elena et al, 2015; Qiu et al, 2015), simple sequence repeat (SSR) or microsatellite (Begoude Boyogueno et al, 2012; Bihon et al, 2011, 2012b; Rêgo et al, 2019), and universally primed polymerase chain reaction (UP‐PCR; Baskarathevan et al, 2012; Billones‐Baaijens et al, 2013). Most of the studies have revealed low genetic differentiation among populations collected from different woody plants or geographic regions (Al‐Sadi et al, 2013; Begoude Boyogueno et al, 2012; Elena et al, 2015; Rêgo et al, 2019), although significant genetic differentiation has also been reported in D. pinea (Bihon et al, 2012b) and D. seriata (Qiu et al, 2015) populations in South Africa and Australia, respectively. Despite homogeneity across regions, marker analyses have revealed distinct genetic clusters within populations of D. seriata (Elena et al, 2015) and L. theobromae (Rêgo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations